ChemInform Abstract: Stereoisomers of Ieodoglucomides A and B: Synthesis and Evaluation of Anticancer Activity. Issue 35 (2nd September 2014) - Reddy, Chada Raji; Jithender, Enukonda; Singh, Ashita; Ummanni, Ramesh
Abstract The alpha‐isomers (Ia) and (Ib) of ieodoglucosamides A and B as well as their C14‐epimers (II) are prepared from glucose and tested on their anticancer activity (prostate cancer DU145, human lung carcinoma A549, breast cancer MCF‐7, human epithelial cervical cancer HeLa cells).